2017
DOI: 10.1210/jc.2016-3222
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Mucosa of Patients With Type 1 Diabetes Shows Distinctive Inflammatory Profile and Microbiota

Abstract: This study shows that duodenal mucosa in T1D presents disease-specific abnormalities in the inflammatory profile and microbiota. Understanding the mechanisms underlying these features is critical to disentangle the complex pathogenesis of T1D and to gain new perspectives for future therapies targeting the intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 37 publications
8
98
0
2
Order By: Relevance
“…As the microbiome is highly influential in the development and activity of the immune system within the gut, researchers have sought to determine the role of intestinal immune function in the development of T1D. In humans with T1D, duodenal samples had increased expression of pro-inflammatory cytokines, increased leukocytic infiltration, as well as alterations in microbial populations within the microbiome (increase in Firmicutes), which all contributed to a pro-inflammatory environment as compared to healthy controls [201]. …”
Section: Barrier Pathophysiology In Diseasementioning
confidence: 99%
“…As the microbiome is highly influential in the development and activity of the immune system within the gut, researchers have sought to determine the role of intestinal immune function in the development of T1D. In humans with T1D, duodenal samples had increased expression of pro-inflammatory cytokines, increased leukocytic infiltration, as well as alterations in microbial populations within the microbiome (increase in Firmicutes), which all contributed to a pro-inflammatory environment as compared to healthy controls [201]. …”
Section: Barrier Pathophysiology In Diseasementioning
confidence: 99%
“…The COX2 and NOS3 gene polymorphisms alter COX2 and NOS3 gene expression, as well as cyclooxygenase and nitric oxide synthesis. Cyclooxygenase and nitric oxide are important mediators of the inflammatory response in diabetes . Low grade inflammation has been shown to play a significant role in the pathogenesis of GDM …”
Section: Discussionmentioning
confidence: 99%
“…During the 1970s and 1980s, Staphylococcus aureus was unusual in the infantile intestinal microflora in Sweden; in sharp contrast, this bacteria today occurs in high numbers in the intestinal flora of 70% of Swedish children during their first year of life . Similarly, a recent study of duodenal biopsies from people with longstanding T1D showed an increased ratio of Firmicutes/Bacteroidetes, mainly because of an increase in bacilli ( Streptococcus ) . The authors concluded that a specific microbial composition of the duodenal mucosa could be a pathogenic feature of T1D .…”
Section: Why Are Other Mammals Not Affected By the Characteristic T1dmentioning
confidence: 97%